Easy drawing : simple step-by-step lessons for learning to draw in more than just pencil - Ward, Chelsea (Art made easy (Walter Foster (Firm)), 2022)
Easy Drawing offers beginning artists a definite way to succeed. Without getting bogged down in a lot of technical detail, artists just need to gather a few inexpensive supplies and put graphite pencil or colored pencil to paper!